Coping with Anxiety: Lived Experiences of Final Year Students - Syed Mahmood, Syarifah Rohaniah; Nizam, Fatin Afiqah; Ismail, Halim; Abdallah, Ssekamanya Siraje; Ahmad, Noorlila (Asian Social Work Journal, 2025)
The prevalence of anxiety has been increasing gradually over the years, becoming one of the most critical issues in colleges and universities. A phenomenological approach was used to explain how final-year undergraduate students experienced anxiety during their internship. In-depth interviews were conducted with four female final-year students at a Public Institution of Higher Education (PIHE) in Klang Valley, Kuala Lumpur, Malaysia. The findings revealed that anxiety affected the students in three aspects: physical, mental, and emotional. In coping with anxiety, five strategies were employed, which are staying connected with others, taking care of physical health, taking time out, using structured problem-solving, and writing expressive journals.